Differences between Australian triathlon coaching practices and evidence-based training load management recommendations - Wells, L. A.; Bruce, L.; Hoffmann, S. M.; Kremer, P.; Dwyer, D. B. (International Journal of Sports Science & Coaching, 2024)
Objectives The training load practices of triathlon coaches are poorly understood. The aim of this study was to explore and describe these practices to create an opportunity to compare their alignment with evidence-based practices.